2024
DOI: 10.1182/blood.2023021567
|View full text |Cite
|
Sign up to set email alerts
|

Durable response after tisagenlecleucel in adults with relapsed/refractory follicular lymphoma: ELARA trial update

Martin Dreyling,
Nathan Hale Fowler,
Michael Dickinson
et al.

Abstract: Tisagenlecleucel is approved for adults with relapsed/refractory (r/r) follicular lymphoma (FL) in the ≥3rd-line setting. The primary analysis (median follow-up: 17 months) of the Phase II ELARA trial (ClinicalTrials.gov identifier: NCT03568461) reported high response rates and excellent safety profile in extensively pretreated patients with r/r FL. Here we report longer-term efficacy, safety, pharmacokinetic, and exploratory biomarker analyses after a median follow-up of 29 months. As of March 29, 2022, 97 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…The prevalence of G3/4 cytopenia at D90 was 26% in the pivotal trial of brexucabtagene autoleucel (brexu-cel) for R/R mantle cell lymphoma (MCL), and in the RWE, the prevalence of G3/4 neutropenia and thrombocytopenia at D90 was 18% and 11%, respectively. In pivotal trials of CART19 for R/R follicular lymphoma (FL), the prevalence of D90 G3/4 cytopenia was 6% with axi-cel, and the probability of G3/4 cytopenia at 6 months was 18% with tisa-cel ( Table 1 ) ( 1 , 7 , 11 , 23 25 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of G3/4 cytopenia at D90 was 26% in the pivotal trial of brexucabtagene autoleucel (brexu-cel) for R/R mantle cell lymphoma (MCL), and in the RWE, the prevalence of G3/4 neutropenia and thrombocytopenia at D90 was 18% and 11%, respectively. In pivotal trials of CART19 for R/R follicular lymphoma (FL), the prevalence of D90 G3/4 cytopenia was 6% with axi-cel, and the probability of G3/4 cytopenia at 6 months was 18% with tisa-cel ( Table 1 ) ( 1 , 7 , 11 , 23 25 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Basis der Zulassungen durch EMA und FDA für beide Präparate waren einarmige Studien, die eine gute Wirksamkeit der Therapie mit Ansprechraten > 80 % und Vollremissionen in >⅔ aller behandelten Patienten zeigten. In Anbetracht der Erkrankungskinetik von FL sind die Nachbeobachtungszeiten der Studien immer noch relativ kurz, zeigen jedoch langanhaltende Remissionen bei einem Teil der Patient*innen (mediane Remissionsdauer für Axi-cel 38,6 Monate, für Tisa-cel nicht erreicht [13,14]). Retrospektive Propensity-Score-gematchte Vergleiche mit historischen Kohorten deuten zudem auf eine bessere Wirksamkeit der CAR-T-Zell-Therapie im Vergleich zum bisherigen Therapiestandard hin [15,16] Merke Bispecifics stellen damit eine aussichtsreiche Therapiestrategie nach Versagen einer CD19-CAR-T-Zell-Therapie dar [20,21].…”
Section: Merkeunclassified
“…The primary analysis of the Phase II ELARA trial reported high response rates and excellent safety profile in extensively pretreated patients with r/r FL ( 44 ). Findings from a longer-term update of the ELARA trial continue to demonstrate high response rates and durable remissions with a favorable safety profile ( 45 ). No new safety signals were reported.…”
Section: Introductionmentioning
confidence: 99%